A polyionic liquid amphiphilic block copolymer brush and preparation method thereof, and polyionic liquid photonic crystal porous microspheres containing the same

Polyionic liquid amphiphilic block copolymer brushes are prepared by polymerizing norbornene group ionic liquid hydrophilic blocks and hydrophobic blocks, and photonic crystal porous with high specific surface area and high ionic liquid density are prepared using this brush. Microspheres solve the problems of uneven pore sizes and poor porous connectivity of existing materials, and achieve efficient biomolecular loading and storage.

CN118812825BActive Publication Date: 2025-02-14TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410871213.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-02-14
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

The existing polyion liquid materials have problems of uneven pore size and poor pore connectivity in the separation and purification of adsorption pollutants and biomolecules, which limits their further development.

Method used

Polyionic liquid amphiphilic block copolymer brushes are prepared by polymerizing norbornene ionic liquid hydrophilic blocks with hydrophobic blocks, and photons with high specific surface area and high ionic liquid density are prepared using the brush. Crystal porous microspheres.

Benefits of technology

The obtained polyion liquid photon porous microspheres can support the adsorption of biological molecules, are suitable for catalytic synthesis, DNA extraction and DNA information storage, and have high biomolecular loading and long-term stable storage capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812825B_ABST
    Figure CN118812825B_ABST
Patent Text Reader

Abstract

The present invention proposes a polyionic liquid amphiphilic block copolymer brush and a preparation method thereof and a polyionic liquid photonic crystal porous microsphere containing the same, which belongs to the field of photonic crystal microsphere preparation. Specifically, the norbornene-based ionic liquid hydrophilic block is copolymerized with the hydrophobic block through ring-opening metathesis polymerization to obtain a series of amphiphilic block copolymer brushes with different block ratios and different molecular weights; then the brushes are emulsified together with a surfactant aqueous solution, and the organic solvent is volatilized to obtain polyionic liquid photonic crystal porous microspheres. That is, the present invention introduces charged ionic liquids into porous photonic microspheres by polymerizing ionic liquid hydrophilic blocks, which can be used in various fields such as DNA adsorption, DNA encoding, and sewage purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photonic crystal microsphere preparation, and particularly relates to a polyionic liquid amphiphilic block copolymer brush, a preparation method thereof, and polyionic liquid photonic crystal porous microspheres containing the same. Background Art

[0002] Polyionic liquids are the polymerization products of ionic liquid monomers and have become an interdisciplinary research field including polymers, ionic liquids and materials science. The excellent performance and rich chemical structure library have aroused widespread interest among researchers. Ionic liquids have excellent physical and chemical properties, such as good solubility and biocompatibility, low vapor pressure, and non-flammability. Polyionic liquids not only have the precisely adjustable physical and chemical properties of ionic liquids, but also have the inherent properties of polymers such as good mechanical stability and size control. They can be applied to a variety of fields such as environmental protection, catalytic synthesis, DNA extraction, drug delivery and antibacterial treatment.

[0003] In recent years, the self-assembly of amphiphilic block copolymers into porous nanostructured materials has aroused great interest. For example, the prior art (Self-Assembled Photonic Microsensors with Strong Aggregation-Induced Emission for Ultra-Trace Quantitative Detection) records a scheme of using amphiphilic bottle brush block copolymers (BBCP) as surfactants to stabilize water-in-oil-in-water (W / O / W) double emulsion droplets, and preparing photonic crystal porous microspheres with uniform particle size and pore size by a one-step method, and also proves that the photonic crystal porous microspheres prepared in this way can be used for trace detection (ppb level, ng / L) and adsorption of small molecules. However, the polyionic liquid materials currently used for adsorption of pollutants and separation and purification of biomolecules have problems such as uneven pore size and poor porous connectivity, which limits their further development.

[0004] Therefore, there is an urgent need to provide a new type of nanoporous material to achieve rapid adsorption of substances, which is crucial for the development of the field of biomolecule separation. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a polyionic liquid amphiphilic block copolymer brush, a preparation method thereof, and polyionic liquid photonic crystal porous microspheres containing the same.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A method for preparing a polyionic liquid amphiphilic block copolymer brush comprises the following steps:

[0009] The norbornene-based ionic liquid hydrophilic block and the hydrophobic block are subjected to a ring-opening metathesis polymerization reaction under a catalyst condition to prepare a polyionic liquid amphiphilic block copolymer brush;

[0010] Wherein, the structural formula of the norbornene-based ionic liquid hydrophilic block includes:

[0011]

[0012] In the above formula, n=2~400.

[0013] Preferably, the molar ratio of the hydrophobic block, the norbornene-based ionic liquid hydrophilic block and the catalyst is (15-40):(20-320):1.

[0014] Preferably, the reaction conditions during the ring-opening metathesis polymerization reaction are: stirring at room temperature for 2 hours.

[0015] Preferably, the hydrophobic block comprises norbornene-terminated polystyrene, polytert-butyl acrylate, polydimethylsiloxane, polymethyl methacrylate, polymethyl acrylate, polyacrylonitrile, polylactic acid, poly-ε-caprolactone, polyethylene or polypropylene.

[0016] Furthermore, the structural formula of the norbornene-terminated polystyrene is:

[0017]

[0018] In the above formula, m=15-200.

[0019] The second technical solution of the present invention:

[0020] A polyionic liquid amphiphilic block copolymer brush is prepared by the above preparation method.

[0021] Preferably, its structural formula includes any one of the following:

[0022]

[0023] In the above formula, x=15-80; y=20-800; m=15-200; n=2~400.

[0024] Preferably, the molecular weight of the polyionic liquid amphiphilic block copolymer brush is 10×10 4 -50×10 4 g / mol.

[0025] The third technical solution of the present invention:

[0026] A polyionic liquid photonic crystal porous microsphere, the raw materials of which include the polyionic liquid amphiphilic block copolymer brush.

[0027] Preferably, the average specific surface area of ​​the polyionic liquid photonic crystal porous microspheres is 84 cm 3 / g; the average ionic liquid density is 2 mol / mg.

[0028] Beneficial effects: The polyionic liquid photonic porous microspheres prepared by the present invention have high specific surface area and high ionic liquid density, can load and adsorb biological molecules, and are suitable for applications in the fields of catalytic synthesis, DNA extraction and DNA information storage.

[0029] The fourth technical solution of the present invention:

[0030] The above-mentioned polyionic liquid photonic crystal porous microspheres are used in biomolecule loading and DNA information storage.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The polyionic liquid photonic crystal porous microspheres disclosed in the present invention can be used for biomolecule loading and DNA information storage by adding ionic liquid groups to the hydrophilic block to introduce ionic liquids into the porous photonic microspheres, and then through the electrostatic interaction between the charges on the surface of the microspheres and the negative charges of DNA or other biomolecules, rapid adsorption can be achieved. Compared with traditional nanoporous materials, the photonic crystal porous microspheres prepared by the OSE (ordered spontaneous emulsification) mechanism of the present invention have larger micropores and channels, which are convenient for biomolecules to enter.

[0033] Compared with the existing patent CN116474742A, the polyionic liquid photonic crystal porous microspheres prepared by the present invention carry a higher charge per unit mass, and the average charge density can reach 2 mol / mg. The preparation process of the microspheres does not require highly polluting and volatile trimethylamine, and at the same time, large-pore spheres with uniform pore size can be obtained, keeping the structure from collapsing.

[0034] The photonic crystal porous microspheres prepared by the present invention have high specific surface area and high charge, can adsorb biological molecules such as DNA, and are suitable for applications in the fields of biological molecule loading, DNA information storage, etc.

[0035] Existing cationic block copolymers for biomolecule loading still face problems such as insufficient stability and easy aggregation and precipitation from the solution. The present invention improves the long-term stable storage capacity of polyionic liquid photonic porous microspheres for biomolecules by combining a stable polymer skeleton with a high specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0037] Figure 1 This is a schematic diagram of the process of preparing the polyionic liquid photonic crystal porous microspheres of the present invention;

[0038] Figure 2 This is a microscope reflection picture of the polyionic liquid photonic crystal porous microspheres prepared in Example 1-8;

[0039] Figure 3 This is a reflection spectrum diagram of the polyionic liquid photonic crystal porous microspheres prepared in Example 1-8;

[0040] Figure 4 The preservation effect of the polyionic liquid photonic crystal porous microspheres prepared in Example 6 on DNA storing information at room temperature 25°C and humidity 30% RH;

[0041] Figure 5 This is the SEM image of the polyionic liquid photonic crystal porous microspheres prepared in Example 6. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0047] A polyionic liquid amphiphilic block copolymer brush is obtained by polymerizing a norbornene-based ionic liquid hydrophilic block and a hydrophobic block.

[0048] In some preferred embodiments, the norbornene-based ionic liquid hydrophilic block comprises any one of the following structural formulas:

[0049]

[0050] Wherein, n is the degree of polymerization of polyethylene glycol, and n=2-400.

[0051] In some preferred embodiments, the molecular weight of the amphiphilic triblock copolymer brush is 10×10 4 -50×10 4 g / mol, the degree of polymerization of the hydrophobic block is 15-80, and the degree of polymerization of the hydrophilic block of the norbornene-based ionic liquid is 20-800, preferably 60-400.

[0052] In some preferred embodiments, the method for preparing the amphiphilic triblock copolymer brush comprises the following steps:

[0053] The hydrophobic block, the norbornene-based ionic liquid hydrophilic block and the catalyst are mixed in a molar ratio of (15-40):(20-320):1, and polymerization reaction is carried out to obtain an amphiphilic block copolymer brush.

[0054] In some preferred embodiments, the hydrophobic block includes any one of polystyrene, poly-tert-butyl acrylate, polydimethylsiloxane, polymethyl methacrylate, polymethyl acrylate, polyacrylonitrile, polylactic acid, poly-ε-caprolactone, polyethylene or polypropylene;

[0055] The norbornene-based ionic liquid hydrophilic block includes norbornene-containing amino, imidazolyl, pyridyl, quaternary phosphine, pyrrolidinyl or piperidinyl hydrophilic ionic liquids.

[0056] The catalyst is Grubbs third generation catalyst.

[0057] The present invention also discloses a method for preparing polyionic liquid photonic crystal porous microspheres, comprising the following steps:

[0058] The amphiphilic block copolymer brush is dissolved in an organic solvent immiscible with water to form a polymer solution, which is emulsified together with a surfactant aqueous solution, the organic solvent is volatilized, and the solid phase component is collected to obtain the polyionic liquid photonic crystal porous microspheres.

[0059] In some preferred embodiments, the mass concentration of the polymer solution is 1-25 mg / mL.

[0060] In some preferred embodiments, the organic solvent includes any one of toluene, xylene, dichloromethane, chloroform, benzene, n-hexane or petroleum ether.

[0061] In some preferred embodiments, the surfactant includes any one of sodium lauryl sulfate, hexadecyltrimethylammonium bromide, or polyvinyl alcohol;

[0062] The mass fraction of the surfactant aqueous solution is 0.2-20%;

[0063] In some preferred embodiments, the emulsification method is microfluidics, shaking or membrane emulsification.

[0064] A polyionic liquid photonic crystal porous microsphere obtained according to the preparation method; the particle size is 5-100 μm.

[0065] The above-mentioned polyionic liquid photonic crystal porous microspheres are applied in the fields of DNA extraction and DNA information storage.

[0066] The surfactant used in the following embodiments of the present invention is polyvinyl alcohol (PVA), whose molecular weight is 25000 g / mol and molecular weight distribution (PDI) is 2.7. Based on the role of the surfactant in reducing the surface tension and stabilizing the emulsion droplets in the present invention, sodium dodecyl sulfate or hexadecyl trimethyl ammonium bromide can replace polyvinyl alcohol as the surfactant of the present invention to achieve similar technical effects.

[0067] In the following embodiments of the present invention, the organic solvent used in step (2) is toluene. Based on the role of the organic solvent to dissolve the polymer and simultaneously separate the phases with the water layer to form emulsion droplets, replacing it with xylene, dichloromethane, chloroform, benzene, n-hexane or petroleum ether can achieve similar technical effects.

[0068] The hydrophobic block used in the following embodiments of the present invention is polystyrene, specifically norbornene-terminated polystyrene (NB-PS), with a molecular weight of 3300 g / mol. Based on the role of the hydrophobic block to stabilize the emulsion droplets and constitute the skeleton of the photonic crystal porous microspheres, similar technical effects can be achieved by replacing the polystyrene in the embodiments of the present invention with polytert-butyl acrylate, polydimethylsiloxane, polymethyl methacrylate, polymethyl acrylate, polyacrylonitrile, polylactic acid, polyε-caprolactone, polyethylene or polypropylene.

[0069] The preparation steps of the norbornene-based ionic liquid hydrophilic block used in the following embodiments of the present invention are as follows:

[0070] 1. Add 5g of polyethylene glycol monomethyl ether, 5g of triethylamine (TEA) and 200mL of ultra-dry dichloromethane (DCM) to a dry 500mL branch-mouth bottle, stir magnetically to mix evenly, cool in an ice-water bath for 20min, then add 5g of 4-toluenesulfonyl chloride dropwise, and continue to react at room temperature for 16h after the addition. Add 100mL of deionized water to quench the reaction, extract the reaction solution three times with deionized water (3×100mL), saturated sodium carbonate (3×100mL) and saturated sodium chloride solution (3×100mL), separate the lower organic layer, and dry it with anhydrous magnesium sulfate. Finally, the obtained organic solution is filtered to remove anhydrous magnesium sulfate and concentrated to obtain polyethylene glycol p-toluenesulfonate.

[0071] 5 g of p-toluenesulfonic acid polyethylene glycol ester, 5 g of imidazole and 200 mL of ultra-dry dichloromethane (DCM) were added to a dry 500 mL branched bottle and heated at 70°C for 16 h. The reaction solution was extracted three times with deionized water (3×100 mL), saturated sodium carbonate (3×100 mL) and saturated sodium chloride solution (3×100 mL), and the lower organic layer was separated and dried with anhydrous magnesium sulfate. Finally, the obtained organic solution was filtered to remove anhydrous magnesium sulfate and concentrated to obtain imidazolyl polyethylene glycol.

[0072] 5g of 5-norbornene-2-methyl brominated alkyl ester, 5g of imidazolyl polyethylene glycol and 50mL of acetonitrile were added to a 100mL round-bottom flask and stirred at 95°C for 18h for ionization reaction. After the reaction, the acetonitrile solvent was spun out and extracted three times with anhydrous ether (3×100mL) to remove excess alkyl imidazole, and the aqueous phase was collected. After the reaction, the reaction solution was extracted with dichloromethane (3×50mL), the dichloromethane layer was collected, and dried with anhydrous magnesium sulfate. The obtained organic solution was filtered to remove anhydrous magnesium sulfate. Finally, it was concentrated to obtain norbornene-based ionic liquid 1.

[0073] 2. Add 5g of nadic anhydride, 5g of 2-dimethylaminoethylamine and 50mL of toluene to a 100mL round-bottom flask and stir and reflux at 105°C for 8h. After the reaction is completed, spin out the toluene solvent, dissolve it with 50mL of dichloromethane, extract it three times with deionized water (3×100mL), saturated sodium carbonate (3×100mL) and saturated sodium chloride solution (3×100mL), separate the lower organic layer, and dry it with anhydrous magnesium sulfate. Filter the obtained organic solution, remove the anhydrous magnesium sulfate, and concentrate to obtain dimethylamino norbornene.

[0074] Add 5g of dimethylamino norbornene, 5g of brominated polyethylene glycol and 50mL of acetonitrile to a 100mL round-bottom flask and stir and reflux at 95°C for 18h for ionization reaction. After the reaction is completed, the acetonitrile solvent is spun out and extracted three times with anhydrous ether (3×100mL) to remove excess alkylimidazole, and the aqueous phase is collected. After the reaction is completed, the reaction solution is extracted with dichloromethane (3×50mL), the dichloromethane layer is collected, and it is dried with anhydrous magnesium sulfate. The obtained organic solution is filtered to remove anhydrous magnesium sulfate. Finally, it is concentrated to obtain norbornene-based ionic liquid 2.

[0075] 3. Add 5g of polyethylene glycol monomethyl ether, 5g of triethylamine (TEA) and 200mL of ultra-dry dichloromethane (DCM) to a dry 500mL branch-mouth bottle, stir magnetically to mix evenly, cool in an ice-water bath for 20min, add 5g of 4-bromoalkyl chloride dropwise, and continue to react at room temperature for 16h after the addition is complete. Add 100mL of deionized water to quench the reaction, extract the reaction solution with deionized water (3×100mL), saturated sodium carbonate (3×100mL) and saturated sodium chloride solution (3×100mL) 3 times, separate the lower organic layer, and dry it with anhydrous magnesium sulfate. Finally, the obtained organic solution is filtered to remove anhydrous magnesium sulfate, concentrated, and the obtained crude product is further purified by column chromatography, and column chromatography is performed using an eluent with a volume ratio of petroleum ether and ethyl acetate of 4:1, and finally concentrated to obtain bromobutyric acid polyethylene glycol ester.

[0076] Add 5g of dimethylamino norbornene, 5g of polyethylene glycol bromobutyrate and 50mL of acetonitrile to a 100mL round-bottom flask and stir and reflux at 95°C for 18h for ionization reaction. After the reaction is completed, the acetonitrile solvent is spun out and extracted three times with anhydrous ether (3×100mL) to remove excess alkylimidazole, and the aqueous phase is collected. After the reaction is completed, the reaction solution is extracted with dichloromethane (3×50mL), the dichloromethane layer is collected, and it is dried with anhydrous magnesium sulfate. The obtained organic solution is filtered to remove anhydrous magnesium sulfate. Finally, it is concentrated to obtain norbornene-based ionic liquid 3.

[0077] The preparation processes of the above-mentioned norbornene-based ionic liquids 1-3 correspond to the following three synthetic routes respectively;

[0078] The synthetic route is as follows:

[0079]

[0080] The hydrophilic block effect of the norbornene-based ionic liquid in the present invention is to provide ionic liquid for the photonic crystal porous microspheres. Replacing Br with other halogens; replacing the amino group with imidazole, pyridyl, quaternary phosphine, pyrrolidinyl, and piperidinyl can achieve similar technical effects.

[0081] The synthesis route of the amphiphilic block copolymer brush in step (1) of Example 1 of the present invention is as follows:

[0082] Where n = 13;

[0083] The synthesis route of the amphiphilic block copolymer brush in step (1) of Example 9 of the present invention is as follows:

[0084] Wherein n=3; the synthesis route of the amphiphilic block copolymer brush in step (1) of Example 16 of the present invention is:

[0085]

[0086] Where n=91.

[0087] The raw materials used in the following embodiments of the present invention are all commercially available products, and their specific purchase sources are shown in Table 1 below:

[0088] Table 1

[0089]

[0090]

[0091] The technical solution of the present invention is further illustrated by the following embodiments.

[0092] Example 1

[0093] A method for preparing polyionic liquid photonic crystal porous microspheres, the steps are as follows:

[0094] (1) Preparation of amphiphilic block copolymer brushes: polystyrene (NB-PS), Grubbs third-generation catalyst, and norbornene-based ionic liquid hydrophilic block (n=13) were added into a polymerization bottle containing dichloromethane at a molar ratio of 28:1:140, and the mixture was stirred with a magnetic stirrer at room temperature for 2 h to obtain an amphiphilic block copolymer brush containing ionic liquid;

[0095] (2) Preparation of polyionic liquid photonic crystal porous microspheres: The amphiphilic block copolymer brush was dissolved in toluene to prepare a polymer solution with a concentration of 15 mg / mL; the polymer solution was then poured into a 2 wt.% polyvinyl alcohol aqueous solution by microfluidics, emulsified to form emulsion droplets, and then placed at 25°C and 50% RH (humidity) for 25 h to allow the organic solvent toluene to evaporate completely, thereby obtaining polyionic liquid photonic crystal porous microspheres.

[0096] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 1 show purple structural color under normal light, and the average pore size of the microspheres is about 144 nm.

[0097] Example 2

[0098] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 30:1:150, and polyionic liquid photonic crystal porous microspheres are obtained.

[0099] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 2 show a blue structural color under normal light, and the average pore size of the microspheres is about 172 nm.

[0100] Example 3

[0101] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 31:1:157, and polyionic liquid photonic crystal porous microspheres are obtained.

[0102] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 3 show a blue-green structural color under normal light, and the average pore size of the microspheres is about 206 nm.

[0103] Example 4

[0104] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 33:1:164, and polyionic liquid photonic crystal porous microspheres are obtained.

[0105] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 4 show a green structural color under normal light, and the average pore size of the microspheres is about 216 nm.

[0106] Example 5

[0107] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 36:1:182, and polyionic liquid photonic crystal porous microspheres are obtained.

[0108] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 5 show a yellow structural color under normal light, and the average pore size of the microspheres is about 233 nm.

[0109] Example 6

[0110] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 39:1:192, and polyionic liquid photonic crystal porous microspheres are obtained.

[0111] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 6 show orange structural color under normal light, and the average pore size of the microspheres is about 242 nm.

[0112] Example 7

[0113] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 42:1:211, and polyionic liquid photonic crystal porous microspheres are obtained.

[0114] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 7 show a red structural color under normal light, and the average pore size of the microspheres is about 293 nm.

[0115] Example 8

[0116] The only difference from Example 1 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 48:1:250, and polyionic liquid photonic crystal porous microspheres are obtained.

[0117] The microscopic reflection image of the prepared polyionic liquid photonic crystal porous microspheres is shown in Figure 2 As can be seen from the figure, the polyionic liquid photonic crystal porous microspheres prepared in Example 8 show infrared structural colors under normal light, and the average pore size of the microspheres is about 362 nm.

[0118] Example 9

[0119] The preparation steps of a polyionic liquid photonic crystal porous microsphere are as follows:

[0120] (1) Preparation of amphiphilic block copolymer brushes: Polystyrene (NB-PS), Grubbs third-generation catalyst, and norbornene-based ionic liquid hydrophilic block (n=3) were added into a polymerization bottle containing dichloromethane at a molar ratio of 22:1:152, and the mixture was stirred with a magnetic stirrer at room temperature for 2 h to obtain an amphiphilic block copolymer brush containing an ionic liquid.

[0121] (2) Preparation of polyionic liquid photonic crystal porous microspheres: The amphiphilic block copolymer brush was dissolved in toluene to prepare a polymer solution with a concentration of 15 mg / mL; the polymer solution was then poured into a 2 wt.% polyvinyl alcohol aqueous solution by microfluidics, emulsified to form emulsion droplets, and then placed at 25°C and 50% RH for 25 h to allow the organic solvent toluene to evaporate completely, thereby obtaining polyionic liquid photonic crystal porous microspheres.

[0122] The charged porous microspheres for DNA loading prepared in Example 9 showed purple structural color under normal light, and the average pore size of the microspheres was about 132 nm.

[0123] Example 10

[0124] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 24:1:145, and polyionic liquid photonic crystal porous microspheres are obtained.

[0125] The polyionic liquid photonic crystal porous microspheres prepared in Example 10 showed a blue structural color under normal light, and the average pore size of the microspheres was about 161 nm.

[0126] Embodiment 11

[0127] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 27:1:183, and polyionic liquid photonic crystal porous microspheres are obtained.

[0128] The polyionic liquid photonic crystal porous microspheres prepared in Example 11 show a blue-green structural color under normal light, and the average pore size of the microspheres is about 198 nm.

[0129] Example 12

[0130] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 30:1:211, and polyionic liquid photonic crystal porous microspheres are obtained.

[0131] The polyionic liquid photonic crystal porous microspheres prepared in Example 12 show green structural color under normal light, and the average pore size of the microspheres is about 208 nm.

[0132] Embodiment 13

[0133] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 32:1:228, and polyionic liquid photonic crystal porous microspheres are obtained.

[0134] The polyionic liquid photonic crystal porous microspheres prepared in Example 13 show yellow structural color under normal light, and the average pore size of the microspheres is about 226 nm.

[0135] Embodiment 14

[0136] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 35:1:244, and polyionic liquid photonic crystal porous microspheres are obtained.

[0137] The polyionic liquid photonic crystal porous microspheres prepared in Example 14 showed orange structural color under normal light, and the average pore size of the microspheres was about 238 nm.

[0138] Embodiment 15

[0139] The only difference from Example 9 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 37:1:260, and polyionic liquid photonic crystal porous microspheres are obtained.

[0140] The polyionic liquid photonic crystal porous microspheres prepared in Example 15 show a red structural color under normal light, and the average pore size of the microspheres is about 289 nm.

[0141] Example 16

[0142] The preparation method of polyionic liquid photonic crystal porous microspheres is as follows:

[0143] (1) Preparation of amphiphilic block copolymer brushes: Polystyrene (NB-PS), Grubbs third-generation catalyst, and norbornene-based ionic liquid hydrophilic block (n=91) were added into a polymerization bottle containing dichloromethane in a molar ratio of 22:1:22, and the mixture was stirred with a magnetic stirrer at room temperature for 2 h to obtain an amphiphilic block copolymer brush containing an ionic liquid.

[0144] (2) Preparation of polyionic liquid photonic crystal porous microspheres: The amphiphilic block copolymer brush was dissolved in toluene to prepare a polymer solution with a concentration of 15 mg / mL; the polymer solution was then poured into a 2 wt % polyvinyl alcohol aqueous solution by microfluidics, emulsified to form emulsion droplets, and then placed at 25°C and 50% RH for 25 h to allow the organic solvent toluene to evaporate completely, thereby obtaining polyionic liquid photonic crystal porous microspheres.

[0145] The charged porous microspheres for DNA loading prepared in Example 16 showed purple structural color under normal light, and the average pore size of the microspheres was about 135 nm.

[0146] Embodiment 17

[0147] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 24:1:24, and polyionic liquid photonic crystal porous microspheres are obtained.

[0148] The polyionic liquid photonic crystal porous microspheres prepared in Example 17 show a blue structural color under normal light, and the average pore size of the microspheres is about 165 nm.

[0149] Embodiment 18

[0150] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 27:1:27, and polyionic liquid photonic crystal porous microspheres are obtained.

[0151] The polyionic liquid photonic crystal porous microspheres prepared in Example 18 showed a blue-green structural color under normal light, and the average pore size of the microspheres was about 201 nm.

[0152] Embodiment 19

[0153] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 30:1:30, and polyionic liquid photonic crystal porous microspheres are obtained.

[0154] The polyionic liquid photonic crystal porous microspheres prepared in Example 19 showed green structural color under normal light, and the average pore size of the microspheres was about 210 nm.

[0155] Embodiment 20

[0156] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 32:1:32, and polyionic liquid photonic crystal porous microspheres are obtained.

[0157] The polyionic liquid photonic crystal porous microspheres prepared in Example 20 showed yellow structural color under normal light, and the average pore size of the microspheres was about 223 nm.

[0158] Embodiment 21

[0159] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 35:1:35, and polyionic liquid photonic crystal porous microspheres are obtained.

[0160] The polyionic liquid photonic crystal porous microspheres prepared in Example 21 show orange structural color under normal light, and the average pore size of the microspheres is about 240 nm.

[0161] Embodiment 22

[0162] The only difference from Example 16 is that the molar ratio of polystyrene (NB-PS), Grubbs third generation catalyst, and norbornene-based ionic liquid hydrophilic block is 37:1:37, and polyionic liquid photonic crystal porous microspheres are obtained.

[0163] The polyionic liquid photonic crystal porous microspheres prepared in Example 22 show red structural color under normal light, and the average pore size of the microspheres is about 282 nm.

[0164] Comparative Example 1

[0165] The only difference from Example 1 is that the hydrophilic block is a polyethylene glycol brush polymer without ionic liquid (purchased from Sigma-Aldrich, monomer molecular weight 550, purity 98%). Porous microspheres for DNA loading are obtained. The average pore size of the microspheres is 152 nm; the particle size is 32 μm; and the reflection wavelength is 402 nm.

[0166] Comparative Example 2

[0167] The only difference from Example 1 is that the norbornene-based ionic liquid is replaced with polylysine (molecular weight 3 kDa), and charged microspheres for DNA loading are obtained. The average pore size of the microspheres is 168 nm; the particle size is 41 μm; and the reflection wavelength is 432 nm.

[0168] Comparative Example 3

[0169] The only difference from Example 9 is that the hydrophilic block is a triethylene glycol linear polymer without ionic liquid (purchased from Hiens, purity 97%), and the porous microspheres for DNA loading are obtained. The average pore size of the microspheres is 308 nm; the particle size is 39 μm; and there is no obvious reflection peak.

[0170] Comparative Example 4

[0171] The only difference from Example 16 is that polystyrene is replaced by an equal molar amount of polymethyl acrylate (molecular weight 5 kDa), and charged porous microspheres for DNA loading are obtained. The average pore size of the microspheres is 236 nm; the particle size is 30 μm; and the reflection wavelength is 520 nm.

[0172] Effect verification

[0173] Effect Example 1

[0174] The present invention conducted the following tests on Examples 1-22. The test results are shown in Tables 2 and Figure 3 shown.

[0175] Table 2

[0176]

[0177]

[0178] Figure 3 The reflection spectrum of the polyionic liquid photonic crystal porous microspheres prepared in Example 1-8 is shown in FIG. Figure 3 It can be seen that the polyionic liquid photonic crystal porous microspheres prepared in Examples 1-8 all produced strong reflection peaks, which is mainly due to the strong Bragg reflection produced by the ordered arrangement of nanopores. And with the increase of norbornene-based ionic liquid hydrophilic blocks, the reflection peak gradually red-shifted, which is mainly caused by the increase in the pore size of the porous microspheres.

[0179] Effect Example 2

[0180] In order to verify the adsorption performance of the polyionic liquid photonic crystal porous microspheres prepared by the present invention on biomolecules, taking DNA as an example, the porous microspheres prepared in Examples 1-6 and Comparative Examples 1-4 and the amphiphilic block copolymer brush prepared in Example 6 were subjected to the following tests:

[0181] The above microspheres or copolymer brushes were respectively configured into 4 mg / mL aqueous suspensions, and then mixed with 0.4 mg / mL DNA solution in equal volumes and allowed to stand at room temperature. The DNA concentration of the supernatant in the mixed solution was measured with a Nanodrop instrument over time to characterize the DNA adsorption kinetic curve of the microspheres. The DNA used was commercial DNA from salmon sperm, Sigma-aldrich, CAS No. 100403-24-5, and the adsorption data was calculated from the difference in supernatant concentration. The test results are shown in Table 3.

[0182] Table 3

[0183]

[0184] Figure 4 The information loss rate of the polyionic liquid photonic crystal porous microspheres for information storage DNA prepared in Example 6. The leftmost column represents the original information storage DNA. The columns from left to right are the information storage DNA loss rates after adsorption, storage, release and amplification by the microspheres at room temperature 25°C and humidity 30% RH for 0-70 (0, 7, 14, 70) days. Figure 4 It can be seen that the microspheres will not damage DNA and have a good preservation effect on DNA.

[0185] Figure 5 This is a SEM image of the polyionic liquid photonic crystal porous microspheres prepared in Example 6. It can be seen from the image that the porous structure is uniform and the connectivity is good.

[0186] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a polyionic liquid amphiphilic block copolymer brush, characterized in that: The following steps are involved: The norbornene-based ionic liquid hydrophilic block and the hydrophobic block are subjected to a ring-opening metathesis polymerization reaction under a catalyst condition to prepare a polyionic liquid amphiphilic block copolymer brush; Wherein, the structural formula of the norbornene-based ionic liquid hydrophilic block includes: ,n=13; ,n=3; or , n=91; The hydrophobic block is norbornene-terminated polystyrene with a molecular weight of 3300 g / mol; its structural formula is: ; The molar ratio of the hydrophobic block, the norbornene-based ionic liquid hydrophilic block and the catalyst is (15-40): (20-320):

1.

2. The method for preparing a polyionic liquid amphiphilic block copolymer brush according to claim 1, characterized in that: The reaction conditions during the ring-opening metathesis polymerization reaction are: stirring at room temperature for 2 hours.

3. A polyionic liquid amphiphilic block copolymer brush, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 2.

4. The polyionic liquid amphiphilic block copolymer brush according to claim 3, characterized in that: The molecular weight of the polyionic liquid amphiphilic block copolymer brush is 10×10 4 -50×10 4 g / mol.

5. A polyionic liquid photonic crystal porous microsphere, characterized in that: The raw materials include the polyionic liquid amphiphilic block copolymer brush according to claim 3.

6. Application of the polyionic liquid photonic crystal porous microspheres as described in claim 5 in biomolecule loading and DNA information storage.

Citation Information

Patent Citations

  • Macromonomer derived from norbornene-based monomer having halogen group capable of inducing radical polymerization at its terminal, norbornene polymer having group capable of inducing radical polymerization at side chain and norbornene polymer produced by graft reaction of the macromonomer using acrylate monomer or styrene monomer, and method for producing them

    JP2005126598A

  • Brush block copolymer comprising functional groups and photonic crystal structure comprising the same

    KR102158611B1